2016
DOI: 10.1017/s1743923x16000246
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender Stereotypes on Voting for Women Candidates by Level and Type of Office

Abstract: Previous research has documented that the public often views women candidates through the lens of gender stereotypes. However, as much of this work draws on experimental designs and hypothetical candidates, we have less information about whether and how voters employ stereotypes in the face of real candidates for office. This project examines one important aspect of the impact of stereotypes on the fate of actual women candidates: whether gender stereotypes have a different influence on elections for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
2
40
1
1
Order By: Relevance
“…This study seeks to enhance the knowledge of how gender stereotypes interact with media coverage, as recent research suggests that the dynamics of gender stereotypes on the campaign trail are changing. 8,16 While research from the 1990s and early 2000s clearly indicated that gender stereotypes played a role in shaping how women candidates across different levels of office were perceived, 17, 18 more recent studies indicate that the prevalence of gender stereotypes, and their influence on women's electoral fortunes is declining. 8,16 Additionally, Dolan and Lynch find that feminine stereotypes affect women candidates differently, depending on the candidate's partisanship.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This study seeks to enhance the knowledge of how gender stereotypes interact with media coverage, as recent research suggests that the dynamics of gender stereotypes on the campaign trail are changing. 8,16 While research from the 1990s and early 2000s clearly indicated that gender stereotypes played a role in shaping how women candidates across different levels of office were perceived, 17, 18 more recent studies indicate that the prevalence of gender stereotypes, and their influence on women's electoral fortunes is declining. 8,16 Additionally, Dolan and Lynch find that feminine stereotypes affect women candidates differently, depending on the candidate's partisanship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…8,16 While research from the 1990s and early 2000s clearly indicated that gender stereotypes played a role in shaping how women candidates across different levels of office were perceived, 17, 18 more recent studies indicate that the prevalence of gender stereotypes, and their influence on women's electoral fortunes is declining. 8,16 Additionally, Dolan and Lynch find that feminine stereotypes affect women candidates differently, depending on the candidate's partisanship. 16 This study focuses on gubernatorial campaigns between 2004 and 2014 to explore the changing media landscape for women running for executive positions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There remain substantial gender differences in modern democracies pertaining to representation, although women generally perform as well as their male counterparts in similar types of electoral races (Darcy, Welch and Clark, 1994). Recent research has found little evidence to support previous claims that voters employ gender stereotypes when they evaluate women candidates (Dolan and Lynch, 2016). Furthermore, no financial disadvantages appear to constrain women candidates in particular (Hogan, 2007;Werner, 1997).…”
Section: Gender Representation As a Function Of The Equalization Persmentioning
confidence: 85%
“…Even though progress has been made towards decreasing the gender disparity among public officials at many levels of government [17], it is important to measure, track, and understand how this disparity is changing over time [52]. Specifically, it is important to unpack to what extent the projection of gender stereotypes onto congressional candidates is being perpetuated during national elections [13,16,18,25,26].…”
Section: Introductionmentioning
confidence: 99%